The Development Of Panenjoan Tour In Jemah Village In Jatigede Waduk Coastal, Sumedang District - Karto Wijaya; Dedi Sugandi (Indonesian Journal of Built Environmental and Sustainability, 2020)
The tourist Panenjoan is an area that is left from water reservoir tofografi Jatigede because having the condition between high so it this area to the shore from Jatigede reservoir, “panenjoan” is terms of language in the sunda or in bahasa means the Place to Look or Gaze. The region of origin is agricultural land belonging to the village in governance changes function into a tourism attraction in governance by the village (BUMDES) or village owned enterprises, the location of that tourism is on the east side Jatigede reservoir inundation area, which is the village scope Jemah, Burujul Hamlet, Jatigede Sub District, Sumedang. The Region Panenjoan tourism is made of this area is the high so that it may become a location can see thoroughly to the inundation of Jatigede reservoir, so it will be for the tourism attraction a panorama in use by visitors as the locations to selfie. With the background Jatigede reservoir area. In the tourism area that made the relative of the who is ± 270 m2 with facility such as mosques, a public toilet, stalls, gazebo sited, and there is a location in designation as a picture.